Evaluation of the curative effects of Bailing capsules for treating chronic obstructive pulmonary disease: A protocol for systematic review and meta-analysis. Issue 25 (25th June 2021) - Zhang, Long; Zhao, Yumiao; Jia, Junli; Huang, Lisha; Chu, Weili; Xu, Qinfu; Sheng, Yanbing; Xu, Aiguo
Abstract: Background: The goal of the present study is to evaluate the efficacy and safety of Bailing capsules, which is a traditional Chinese drug that can improve lung functionality when used to treat chronic obstructive pulmonary disease (COPD) patients. Methods: A comprehensive search will be performed on the following primary electronic databases: PubMed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure, and WanFang database. A search of secondary sources includes reference lists of included studies. Two pairs of review authors will screen and scrutinize selected articles. This study will analyze continuous data as mean differences and dichotomous data as odds ratios, both with 95% confidence intervals. A sensitivity analysis will also be conducted to evaluate the stableness of the outcomes. RevMan 5.3 software was adopted to accomplish all the statistical analysis. Results: The results obtained in this research shall be published in a peer-reviewed journal. Conclusion: Based on the interpretations of the results, useful conclusions will be presented. These conclusions will offer additional insights with useful evidence to assess whether it is viable to use Bailing capsules as an effective and safety treatment option for COPD. Ethics and dissemination: The present work does not involve any humans or animals; therefore, ethical approval is not needed. Systematic review registration: March 26, 2021.osf.io/kvgbu. (https://osf.io/kvgbu/ )